1978
DOI: 10.1136/adc.53.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Fat embolism in infancy after intravenous fat infusions.

Abstract: SUMMARY Four cases of fat embolism are described in infants receiving prolonged intravenous infusion of fat (Intralipid 20%). This therapeutic complication has been termed 'fat overloading syndrome' but bears a clinical similarity to post-traumatic fat embolism. These 4 cases are the first to be recorded in infancy, and with histopathological proof of fat embolism. Transient high rates of infusion of Intralipid appears to be a factor in the aetiology of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 12 publications
0
21
1
1
Order By: Relevance
“…The child developed pneumonia, but an open lung biopsy failed to reveal the cause and the organism was cultured only after the child's death. Previously, it had been demonstrated that intravenous administration of fat emulsions lead to the deposition of lipid deposits within the pulmonary vasculature (40,102,151,251). At autopsy, Malassezia was found within the lipid deposits in the intima and vessel wall of the pulmonary artery and the surrounding lung tissue.…”
Section: Systemic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The child developed pneumonia, but an open lung biopsy failed to reveal the cause and the organism was cultured only after the child's death. Previously, it had been demonstrated that intravenous administration of fat emulsions lead to the deposition of lipid deposits within the pulmonary vasculature (40,102,151,251). At autopsy, Malassezia was found within the lipid deposits in the intima and vessel wall of the pulmonary artery and the surrounding lung tissue.…”
Section: Systemic Diseasesmentioning
confidence: 99%
“…Reduced clearance of lipid in premature and acutely ill neonates (17,174), increased risk of kernicterus in jaundiced neonates (18), potentially increased risk of coronary vascular disease (238), altered prostaglandin synthesis and turnover (151), and deposition of lipid within macrophages leading to altered immunity (227,329) have all been reported. Additionally, deposition of lipid occurs in the lungs of infants receiving lipid emulsions (40,102,251), which may exacerbate preexisting respiratory problems. Therefore, although parenteral nutrition may be essential in providing adequate nutrition for some neonates, its deleterious effects on the immune and other systems further predisposes the infants to infections.…”
Section: Systemic Diseasesmentioning
confidence: 99%
“…Diversos estudos sugerem que as emulsões intravenosas de gorduras utilizadas na nutrição parenteral total (NPT) estão associadas à gênese de algumas das lesões pulmonares de pacientes graves, sendo relatados êmbolos de gordura na luz de artérias [1][2][3] , capilares 1,2,4-7 e depósitos no citoplasma de macrófagos alveolares 1,2,4,7-9 , células epiteliais alveolares 9 , macrófagos septais, condrócitos da cartilagem brônquica e outras células intersticiais 10 .…”
Section: Introductionunclassified
“…Lipid emulsion has been successful in a neonate 39 with severe cardiac compromise after caudal analgesia with bupivacaine. However, constituting safe dosing lipid therapy regimen is very important in neonates and children because complications from lipid overload have been reported in neonates receiving intravenous nutritional support 40 .…”
Section: The Class Of Recommendations and Level Of Evidence For Each mentioning
confidence: 99%